BF4− as source for the preparation of BF2 bridged copper(II) dimethylglyoxime complexes. Issue 16 (24th June 2022) - Petrikat, Raphael I.; Becker, Sabine
Abstract: The reaction of copper(II) tetrafluoroborate with dimethylglyoxime (H2 dmg) leads to the formation of the dinuclear complexes [Cu2 (dmg)(Hdmg)(EtOH)(H2 dmg)]BF4 (1 ) and [Cu2 (dmg ⋅ BF2 )(Hdmg)(H2 dmg)]BF4 (2 ). In 2, BF2 deriving from BF4 − has been inserted into the oxime groups to form an O, O‐bidentate difluoroboron complex. Co‐crystallization of 1 and 2 impeded a thorough characterization of 2 . In further attempts to prepare pure 2, the difluoroboron complexes [Cu(dmg ⋅ BF2 )2 (MeCN)] (3 ) and [Cu(dmg ⋅ BF2 )(Hdmg)] (4 ) have been obtained. Attempts to isolate the BF2 ‐bridged ligand failed. Even though BF4 − readily is decomposed to formally form BF2 + that is inserted into the resulting complexes and F −, the nascent F − ions are not a suitable F − source for organic fluorination reactions. Nevertheless, the described, facile route to prepare O, O‐bidentate difluoroboron complexes without the usage of the highly toxic BF3  ⋅ OEt2 but BF4 − instead is of interest for synthetically working chemists. Abstract : The reaction of Cu(BF4 )2 ⋅6H2 O with dimethylglyoxime affords a series of dinuclear and mononuclear complexes with O, O‐bidentate difluoroboron ligands.